ACT-20 PHASE 1/2, PROSPECTIVE, INTERNATIONAL MULTI-CENTER STUDY TO ESTABLISH THE SAFETY AND FEASIBILITY OF BLOOD-BRAIN-BARRIER DISRUPTION COMBINED WITH CARBOPLATIN FOR RECURRENT GLIOBLASTOMA; FIRST CLINICAL EXPERIENCE IN JAPAN. (3rd December 2022) - Kijima, Noriyuki; Kanemoto, Manabu; Oshino, Satoru; Tani, Naoki; Hosomi, Koichi; Okita, Yoshiko; Hirayama, Ryuichi; Tachi, Tetsuro; Kuroda, Hideki; Utsuki, Rena; Kagawa, Naoki; Kishima, Haruhiko
Abstract: The prognosis for glioblastoma is still very poor despite intensive treatment by surgery, radiation, and chemotherapy. One of the reasons for poor prognosis of glioblastoma is blood-brain-barrier (BBB), which limits the delivery of chemotherapeutic agents to the brain. Focused ultrasound (FUS) therapy is approved for essential tremor and Parkinson disease in Japan and preclinical studies suggest low-intensity focused ultrasound (LIFU) administered with microbubbles (MB) can disrupt BBB and can improve the delivery of chemotherapeutic agents. Thus, currently, focused ultrasound therapy has gained attention in neuro-oncology and a number of clinical trials using FUS for the treatment of glioblastoma are underway. Our institutions (Osaka University Hospital and Saito Yukoukai Hospital) are the first in Japan to join the international multicenter study to examine the safety and feasibility of BBB disruption by FUS and MB combined with intravenous carboplatin for the treatment of recurrent glioblastoma. We are planning to enroll one recurrent glioblastoma patient for this study soon. BBB disruption strategies using FUS and MB for the treatment of neuro-oncological disease has potentials to improve the outcome of patients and many clinical trials will be performed in future.